2021
DOI: 10.3390/met11081200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn Content on the Reaction between Fe-xMn (x = 5, 10, 15, and 20 Mass pct) Steel and CaO-SiO2-Al2O3-MgO Slag

Abstract: Medium- and high-Mn steels have excellent properties but are very difficult to be commercially produced because of the high content of some alloy elements. To enhance the understanding of the reaction between medium/high-Mn steel and refining slag which is significantly different from the conventional steels, steel and slag composition and the inclusions were investigated by equilibrium reaction between Fe-xMn (x = 5, 10, 15, and 20 mass pct) and CaO-SiO2-Al2O3-MgO top slag at 1873 K in the laboratory. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…However, few researchers have been able to draw on any systematic research into the Mn content in the Fe–Mn–Al–C steels. [ 14,18–21 ] So far, very little attention has been paid to how Mn content affects inclusions formation and growth in Fe–Mn–Al–C steels, especially under high aluminum content. Park et al [ 14 ] studied the formation of inclusions in Fe–(10–20)Mn–(1–6)Al steels and found that the Mn content increased from 10% to 20%, Al 2 O 3 , MnAl 2 O 4 , oxide core with MnS, and MnS with AlON inclusions increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few researchers have been able to draw on any systematic research into the Mn content in the Fe–Mn–Al–C steels. [ 14,18–21 ] So far, very little attention has been paid to how Mn content affects inclusions formation and growth in Fe–Mn–Al–C steels, especially under high aluminum content. Park et al [ 14 ] studied the formation of inclusions in Fe–(10–20)Mn–(1–6)Al steels and found that the Mn content increased from 10% to 20%, Al 2 O 3 , MnAl 2 O 4 , oxide core with MnS, and MnS with AlON inclusions increased.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thermodynamic calculations pointed out that the AlN‐containing inclusions, during the cooling and solidification of the steel, are formed. Under the condition of top slag, Yu et al [ 20 ] investigated the effect of CaO–SiO 2 –Al 2 O 3 –MgO slag on the solute elements and inclusions in Fe– x Mn ( x = 10 and 20 wt%) steel. It was observed that large‐sized inclusions decreased and steel cleanliness improved greatly after CaO–SiO 2 –Al 2 O 3 –MgO slag was added, under aluminum‐free conditions.…”
Section: Introductionmentioning
confidence: 99%